2016
DOI: 10.1002/adhm.201600948
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Interactions with Immobilized Liquid Layers

Abstract: Bacterial interactions with surfaces are at the heart of many infection-related problems in healthcare. In this work, the interactions of clinically relevant bacteria with immobilized liquid (IL) layers on oil-infused polymers are investigated. Although oil-infused polymers reduce bacterial adhesion in all cases, complex interactions of the bacteria and liquid layer under orbital flow conditions are uncovered. The number of adherent Escherichia coli cells over multiple removal cycles increases in flow compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
7
49
0
Order By: Relevance
“…Bacterial motility constitutes a critical virulence factor in bacterial colonization by initiating the contact of bacterial cells with surfaces. 8 A recent study 31 has paid attention to the role of bacterial morphology in adhesion to immobilized liquid layers under dynamic conditions, advocating the more efficient adhesion of E. coli cells in comparison with that of S. aureus and P. aeruginosa, under dynamic conditions, to the flagella of E. coli. Furthermore, the most predominant clinical bacteria involved in orthopedic implant infections belong to the Staphylococcus genus followed by Enterobacteriaceae genus.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial motility constitutes a critical virulence factor in bacterial colonization by initiating the contact of bacterial cells with surfaces. 8 A recent study 31 has paid attention to the role of bacterial morphology in adhesion to immobilized liquid layers under dynamic conditions, advocating the more efficient adhesion of E. coli cells in comparison with that of S. aureus and P. aeruginosa, under dynamic conditions, to the flagella of E. coli. Furthermore, the most predominant clinical bacteria involved in orthopedic implant infections belong to the Staphylococcus genus followed by Enterobacteriaceae genus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while dense bacterial attachment almost invariably leads to biofilm formation on synthetic solid surfaces, this may not be the case on a liquid surface. In a recent study, silicone‐oil‐infused PDMS showed a significant number of E. coli colony‐forming units, comparable to noninfused PDMS, under orbital flow, despite preventing all attachment under static conditions . Yet surprisingly, the infused PDMS samples still showed minimal biofilm coverage under both flow and static conditions, suggesting that the progression to biofilm formation may have been blocked.…”
Section: Mechanisms Of Biological Matter Interaction With Slippery Sumentioning
confidence: 95%
“…Solids textured by LbL deposition, UV‐initiated polymerization, or osmotically driven wrinkling and coated with either perfluorinated or silicone liquids have also proven generally effective at resisting both bacterial and fungal biofilm adhesion, frequently preventing more than 97% of the biofilms from remaining on the surfaces ( Figure A,B). Multiple reports have also demonstrated the ability of silicone‐oil‐infused PDMS and other silicone compounds, separately already widely used in medicine, to resist S. aureus , P. aeruginosa , and E. coli biofilm attachment under both static and flow conditions (Figure C) …”
Section: Mechanisms Of Biological Matter Interaction With Slippery Sumentioning
confidence: 97%
See 1 more Smart Citation
“…The same authors also demonstrated higher number of adhered bacteria cultured under dynamic conditions in comparison to the static conditions. [98] An excellent review about antiadhesion properties of SLIPS for medical applications including antibacterial and antithrombogenic uses of SLIPS has been recently published by Sotiri et al [15] SLIPS based on medically relevant materials (such as expanded polytetrafluoroethylene and perfluoroperhydrophenanthrene) was prepared, coated onto the implant surface, and then studied in a rat model. [95] The prepared SLIPS showed good in vivo stability and could enable bacterial elimination at the implant surface, while showing low innate immune response as well as reduced inflammatory capsule formation.…”
Section: Cell-repellent and Antibiofouling Slipsmentioning
confidence: 99%